2019
DOI: 10.3389/fonc.2019.00058
|View full text |Cite
|
Sign up to set email alerts
|

Immune Modulation in HLA-G Expressing Head and Neck Squamous Cell Carcinoma in Relation to Human Papilloma Virus Positivity: A Study From Northeast India

Abstract: Background: Tumor specific ectopic expression of the immunomodulatory molecule, HLA-G is known to mediate immune tolerance and promote carcinogenesis. Viruses too employ strategies to evade immune surveillance. Considering the role of both HLA-G and HPV in tumor growth and progression, it is pertinent to investigate the relationship between HLA-G and HPV in context of immune modulation in HNSCC. Method: A hospital based case–control study was conducted in histopathologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 40 publications
(39 reference statements)
0
18
0
Order By: Relevance
“…KIR2DL4 is expressed by NK cells and a subset of T cells [ 23 , 24 ], and has been shown to induce the inhibition of immune functions of these cells [ 25 , 26 ] as well as activation [ 27 ] upon binding with HLA-G. For instance, a study by Rajagopalan et al reported that soluble HLA-G induced a proinflammatory response via KIR2DL4 in resting NK cells [ 27 ]. The heterogeneous expression patterns of the different isoforms of HLA-G [ 10 , 28 ] and their receptors [ 29 , 30 , 31 ] suggest a fine-tuned network which is closely involved in the regulation of immune interactions. Unfortunately, little is known about the signaling pathways regulating this network.…”
Section: Receptors Of Hla-gmentioning
confidence: 99%
See 1 more Smart Citation
“…KIR2DL4 is expressed by NK cells and a subset of T cells [ 23 , 24 ], and has been shown to induce the inhibition of immune functions of these cells [ 25 , 26 ] as well as activation [ 27 ] upon binding with HLA-G. For instance, a study by Rajagopalan et al reported that soluble HLA-G induced a proinflammatory response via KIR2DL4 in resting NK cells [ 27 ]. The heterogeneous expression patterns of the different isoforms of HLA-G [ 10 , 28 ] and their receptors [ 29 , 30 , 31 ] suggest a fine-tuned network which is closely involved in the regulation of immune interactions. Unfortunately, little is known about the signaling pathways regulating this network.…”
Section: Receptors Of Hla-gmentioning
confidence: 99%
“…Furthermore, RT-qPCR has been used to study HLA-G isoform mRNA expression. For instance, Sarmah et al reported on HLA-G isoform frequency in 35 head and neck squamous cell carcinoma patients [ 28 ]. We did a similar study in CRC and detected mRNA of HLA-G3 in different samples [ 9 ].…”
Section: Expression Of Hla-g In Cancermentioning
confidence: 99%
“…HLA-G has been also shown to modulate the release of cytokines from peripheral blood mononuclear cells or get modulated by several cytokines such as IL-10 and IFNs 28 . In accordance with this, a study from north-east suggests that IFN-γ expression appeared to be mediated by HLA-G in HNSCC tissues and through regulating HLA-G expression, HPV positive tumors could mediate immune suppression by manipulating SOCS, IFN-γ, IL-10 and cyclin D1 pathways 29 . In view of previous study, we have correlated the proinflammatory (IFN-γ) and anti-inflammatory cytokines (IL-10) with of sHLA-G levels in HNSCC patients.…”
Section: Discussionmentioning
confidence: 59%
“…Next to classical HLA class I antigens, the non-classical HLA-G expression was detected in more than 50% of HNSCC lesions, while healthy controls lacked HLA-G expression [ 51 , 52 , 59 , 60 ]. A higher frequency of HLA-G expression was found in HPV + HNSCC when compared to HPV - HNSCC [ 61 ]. Furthermore, significantly higher HLA-G expression levels were detected in metastases compared to primary tumors [ 62 ].…”
Section: The Role Of Classical and Non-classical Hla Class I Antimentioning
confidence: 99%